Child Recruiting and Using in Civil and International Wars (A Comparative Study Between International Law and Islamic Sharia) - Nabe, L.Dr. Aram Nabe Mohammed Wasani; Mohammed, Asst.L. Dawan Mohammed Jaza (Sulaimani Journal for Humanities, 2025)
This paper is a comparative study between international law and Islamic law that focuses on the issue of engaging children in armed conflicts and also these violations that are committed against them in times of warfare by armed forces. The use and arming of children in war has a long history and has become a threat to children's rights. This has resulted in children being more likely to be the main victims compared to adults. Within the framework of international law and Islamic Sharia, the recruitment of children as fighters by the armed forces and their use in warfare is prohibited in any way. For example, the Islamic State of Iraq and Syria (ISIS) has used thousands of children to commit international crimes such as war crimes and crimes against humanity, while children should be protected and not deprived of their basic rights. Moreover, during international and non-international armed conflict children face killing, wounding, Raping, refugee, and internal displacement. For example, Thousands of children have been killed, injured, displaced, and starved in Gaza during the recent fighting between Hamas and Israel. In this study, the researchers analyze the impact of armed conflict on children's rights during war according to international law and Islamic Sharia, and critically discuss the role of the international community in protecting children from the threats and violations they face. To discuss the violation of children's right during armed conflict from the perspective of international law, researchers focus on Additional Protocol I and II of the Geneva Conventions, Convention on the Rights of Child (CRC), Optional Protocol to CRC, Rome Statute and the Universal Declaration of Human Rights. An academic discussion will also be held from the perspective of Islamic Sharia based on verses of the Holy Qur'an, hadiths of Prophet Muhammad and the opinions of scholars of the Islamic world. The research problem and research questions will be debated which related to the legality, legitimacy, and negative effects of recruiting and abusing children during international and non-international armed conflicts.
Keywords: Armed Conflict; Committing Crime; Using and Recruiting; International Law; Islamic Sharia; Protection Right